2021
DOI: 10.1155/2021/8844502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Modified Atmosphere Packaging on the Quality of Mulberry Fruit (Morus alba L. cv Kokuso 21)

Abstract: The control of temperature and gas composition is essential to maintain the fresh flavor and quality of perishable fruits like mulberry. This study presented a modified atmosphere experiment (MAP) for fresh fruit showing the potential benefits of innovative gas mixing with argon. The effects of MAP were studied on the physicochemical and qualitative attributes of mulberry preserved at 4 ± 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Kader et al (1993) also noticed a highly positive correlation (r 2 =0.97) between invertase activity and the degree of ripeness of blueberry fruit during cold storage designated by lowering of sucrose content. This is due to the breathing processes that use sugars as organic substrate, which is less pronounced in MAP-treated fruit due to the use of gas (Tinebra et al, 2021). So, in MAP fruits gasses decrease the respiration rate, thus decreasing the consumption of substrates, resulting in higher sugar content.…”
Section: Tablementioning
confidence: 99%
“…Kader et al (1993) also noticed a highly positive correlation (r 2 =0.97) between invertase activity and the degree of ripeness of blueberry fruit during cold storage designated by lowering of sucrose content. This is due to the breathing processes that use sugars as organic substrate, which is less pronounced in MAP-treated fruit due to the use of gas (Tinebra et al, 2021). So, in MAP fruits gasses decrease the respiration rate, thus decreasing the consumption of substrates, resulting in higher sugar content.…”
Section: Tablementioning
confidence: 99%
“…A similar study on atemoya fruit showed that TSS was affected by the type of plastic used [10]. The decrease in TSS was due to the breakdown of sugar in the physiological process [11]. Changes in TSS of horticultural products can also be influenced by the occurrence of loss of product water content [12].…”
Section: 3total Soluble Solute (Tss)mentioning
confidence: 94%
“…For this purpose, modified atmosphere packaging (MAP) encompassing low oxygen and increase carbon dioxide (CO 2 ) levels can potentially inhibit enzymatic browning, spoilage, and preserve freshness (Navindra et al., 2009). Nowadays, the prospective advantages of argon (Ar) and other noble inert gases in MAP have drawn considerable scientific interest (Tinebra et al., 2021). This can be confirmed by the fact that European Union recently approved Ar addition in MAP as a substitute of nitrogen (N 2 ); a filler gas commonly used in MAP to stabilize CO 2 volume (Caleb et al., 2013; Tinebra et al., 2021).…”
Section: Anti‐browning Methodsmentioning
confidence: 99%
“…Nowadays, the prospective advantages of argon (Ar) and other noble inert gases in MAP have drawn considerable scientific interest (Tinebra et al., 2021). This can be confirmed by the fact that European Union recently approved Ar addition in MAP as a substitute of nitrogen (N 2 ); a filler gas commonly used in MAP to stabilize CO 2 volume (Caleb et al., 2013; Tinebra et al., 2021). Pressurized Ar treatments have additionally shown capacity to maintain cell integrity and inhibiting production of MDA, but most importantly, the enzymatic activities of catalase and peroxidase in pepper (Meng et al., 2012).…”
Section: Anti‐browning Methodsmentioning
confidence: 99%